Development of the Technology for Manufacturing and Introducing a New Class of Tools with CVD Diamond for Grinding High-Precision Gear Wheels of Special Gear Units - Paschenko, Ye.O.; Kukharenko, S.A.; Riabchenko, S.V.; Bychyhin, V.M.; Shatokhin, V.V. (Science and Innovation, 2024)
Introduction. The trueing tool used by machine-building enterprises of Ukraine creates a fundamental constraint for improving the accuracy of shaping of the working profile of abrasive wheels and, accordingly, the accuracy of the products made with its use. Problem Statement. The tools using CVD diamonds are currently designed by leading foreign developers. This class of CVD diamond trueing tool has never been developed or manufactured in Ukraine. Purpose. To develop a technology for the production of precision products from СVD diamond for grinding the gear wheels of special gear units for the needs of mechanical engineering enterprises. Materials and Methods. Techniques and special stands for precise positioning of elements from CVD diamond and for testing the trueing instrument, methods for determining the structure of metallic bonds. Results. The rational positioning of CVD diamond elements on the cases of complex shapes has been studied. The manufactured tools for abrasive wheel trueing have been finished and tested. It has been shown that the use of such elements provides a high resistance to the erosion influence of sludge in the trueing area and is expedient to be used in contact with the main components of abrasive wheels, due to exceptional tribological characteristics. The use of structured metallic bonds has been shown to provide low vibrations in the trueing area and a stable and reproducible topography of the cutting surface of an abrasive tool with a large number of cutting edges and with the ability to direct the orientation of the edges by selecting optimal trueing conditions. Conclusions. For the first time in Ukraine, the Bakul Institute for Superhard Materials of the NAS of Ukraine has created the truing tools equipped with CVD diamond elements and adapted to the production chains of high-precision gear wheels of gear units with enhanced operational characteristics, which enable replacing the imported parts at the machinebuilding enterprises of Ukraine.